Identification, Documentation and Utilization of Wild Green Leafy Vegetables from Tribal Region of Nashik District - Chavan, S P; Jondhale, A S (Plantae Scientia, 2022)
From many years ago the tribal peoples commonly used numbers of wild leafy vegetables all over the world. Peth and Surgana are well known tribal region from Nashik district. The tribal community from that region was partially or fully dependent on the wild green leafy vegetables to complete their nutritional need. In present study from selected tribal region of Nashik district, a total 61 traditionally used wild green leafy vegetables was identified. Among 61 species, with respect to families Amaranthaceae, Fabaceae and Asteraceae were found to be largest family of wild leafy vegetables with 22 species. Presently because of modernization in agricultural practices, negligence of uncultivated plants, less awareness, illiteracy and sudden environmental changes the naturally grown wild leafy vegetables source was limited. So present study was focused on the identification and conservation of these species for future need.